Association of Serum Osteoprotegerin Levels With Carotid‐Femoral Pulse Wave Velocity in Hypertensive Patients. Issue 4 (19th March 2014) - Wang, Ji‐Hung; Lee, Chung‐Jen; Chen, Mei‐Ling; Yang, Chiu‐Fen; Chen, Yu‐Chih; Hsu, Bang‐Gee
Abstract : Osteoprotegerin (OPG) has been implicated in the process of vascular stiffness. The aim of this study was to evaluate the relationship between fasting serum OPG concentration and carotid‐femoral pulse wave velocity (c‐f PWV) in hypertensive patients. Fasting blood samples were obtained from 184 participants with or without hypertension. c‐f PWV were performed by SphygmoCor system. Serum OPG levels were measured using a commercially available enzyme‐linked immunosorbent assay. Hypertensive patients who had diabetes had higher c‐f PWV levels than those without diabetes ( P =.031). The univariable linear regression analysis showed that age ( P <.001), systolic blood pressure ( P =.003), pulse pressure ( r =0.287; P =.003), log‐BUN ( P =.011), Cre ( P <.001), and log‐OPG concentration ( P <.001) were positively correlated with c‐f PWV levels, while the glomerular filtration rate ( P =.005) and HDL‐C level ( P =.024) was negatively correlated with c‐f PWV levels among the hypertensive patients. Multivariable forward stepwise linear regression analysis of the significant variables also showed that log‐OPG (β=0.312, regression coefficient: 1.736; 95% confidence interval, 0.809–2.663; P <.001) was still an independent predictor of c‐f PWV levels in hypertensive patients. Serum OPG levels positively associated with c‐f PWV levels in hypertensive patients.